Austria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix presents estimates of potential output and the output gap for Austria to identify the scope for sustainable noninflation growth and allow an assessment of the current stance of macroeconomic policies. The estimates of the cyclical fluctuations in Austria are compared with those of the other countries of the European Union to provide the basis for an assessment of the relative economic benefits and constraints for Austria in the context of its participation in European Monetary Union, both in the short and longer term.